Development of Pasteurella multocida loaded alginate based microspheres - Tiyaboonchai, Waree; Nimtrakul, Pataranapa; Limpeanchob, Nanteetip (Asian Health, Science and Technology Reports, 2010)
Microencapsulation of Pasteurella multocida within alginate based microspheres (MSs) for subcutaneous vaccination was accomplished by emulsification-cross-linking technique. Alginate MSs were spontaneously formed by ionic cross-linking using calcium and zinc ions, and further stabilized employing zinc ion. A mean particle size of less than 10 um has been successfully developed using simple mixer and ultrasonic probe. The measured zeta potential of the MSs surface showed negatively charge of -30 mV indicating a strong negative charge at the particle’s surface. A positively charge on MSs surface could be obtained by incubating with poly-L-lysine. Optical microscopy revealed spherical particles with uniformly distribution. The antigen entrapment efficacy of up to 75% was achieved. The slow release of antigen from MSs was observed up to a 6 month period.